Analgesic Efficacy of Spinal Morphine in Comparison With Transversus Abdominis Plane Block for Postoperative Pain Management in Patients Undergoing Cesarean Section Under Spinal Anesthesia: A Randomized Controlled Trial - Jemal, Bedru; Mohammed, Fetiha; Tesema, Hailemariam Getachew; Ahmed, Siraj; Mohammed, Ayub; Regasa, Teshome; Obsa, Mohammed Suleiman (Frontiers in Medicine, 2022)
Abstract Background: Caesarean Section (CS) has been one of the most frequently performed major surgical interventions and causes severe postoperative pain. Spinal opioid & abdominal field block has been investigated as effective analgesia for postoperative pain and reduce the need for systemic medications and associated side effect. The aim of current study is to compare spinal morphine and transversus abdominis plane block for postoperative pain management. Method: In this randomized controlled trial 114 pregnant mothers scheduled for Cesarean section under spinal anesthesia was allocated randomly to receive either spinal morphine 0.1mg (group SM; n 56) or transversus abdominis plane block 20ml of 0.25% (group TAP;n 52). A comparison of numerical variables between study groups was done using unpaired student t-test and Manny-Whitney U test for symmetric and asymmetric data respectively. Time to event variable was analyzed by using Kaplan Meir's survival function. P-value of less than 0.05 was considered as statistically significant. Result: One hundred and fourteen patients were recruited and randomly assigned and received interventions. Among them, One hundred and eight patients completed this study. Time to first analgesic request was significantly shorter in TAP block compared to Spinal morphine. Twenty-four hour median morphine consumption were reduced in spinal morphine group compared to TAP block (p<0.001). Median postoperative pain score during movement and rest shows statistically significant differences between groups (p <0.001). Conclusion: Addition of preservative-free 100µg spinal morphine provides prolonged postoperative analgesia time, superior postoperative analgesia, and less postoperative opioid consumption compared to TAP block. Trial registration number PACTR202002616299138 Keywords: Spinal morphine; TAP; analgesia; cesarean section, postoperative analgesia